OPTIMALISASI PENANGANAN MUATAN DENGAN METODE RELIQUEFACTION GUNA MENGATASI KENAIKAN TEKANAN TANGKI DAN KENAIKAN TEMPERATUR MUATAN DI MT. GAS WALIO - Ferdianto Sigala; Muhammad Syafri Sunusi; Barnabas Fendy Tallu (Faculty of Economics and Business, Universitas Malikussaleh, 2026)
Optimizing cargo handling using the reliquefaction method to address increased tank pressure and cargo temperature on the MT. Gas Walio (supervised by Dr. Capt. H. Muhammad Syafril Sunusi, M.Pd., M.Mar., and Capt. Barnabas Fendy Tallu, M.M.Tr., M.Mar.). This research aims to assess the use and maintenance of the reliquefaction system so that it can be optimally used as a cargo handling facility on LPG vessels. This research was conducted on the MT. Gas Walio during the author's Sea Practice (PRALA) from August 2024 to August 2025. The data obtained in this study were primary data obtained directly from the research site through interviews and direct observation with the ship's captain and engineer. The results showed that there were obstacles in the reliquefaction system, namely decreasing tank pressure and cargo temperature, as well as a lack of officer skills in maintaining the reliquefaction system. This impacted safety and reduced LPG cargo volume. Based on these findings, training on reliquefaction system maintenance and regular monitoring of reliquefaction system issues are necessary to avoid harm to LPG cargo. Keywords: Optimization, Reliquefaction, Tank Pressure, Cargo Temperature Reduction, MT. Gas Walio